Driving the Devil Out: Kenya’s Born-Again Election - Deacon, Gregory (Journal of religion in Africa, 2015)
Neo-Pentecostal or born-again language and understandings are highly prominent in Kenya. They were especially visible during the general election of 2013 in which the victorious Jubilee coalition campaigned using a narrative according to which the nation was being washed clean of past sins, redeemed, and born again. This was attractive to and reflected the desires of Kenyans seeking to move beyond the horrors of the postelection violence that occurred in 2007-2008. This provides an invaluable lens for conceptualising current Kenyan understandings of African Christianity and how these relate to politics and contemporary socioeconomic conditions. More specifically, this paper argues that in 2013 a popular desire for health and wealth, and deference to authority came together with personal but abstract repentance and forgiveness narratives. This contributed to a peaceful election but restricted the means through which criticism might be voiced and helps to maintain structural inequality and impunity.